Presenting the Ideal Model of Digital Governance in the Era of Networked Society - ali nourijani; hosein eslami; sayed alireza afshani; hassan dehghan dehnavi (مطالعات رسانه‌های نوین, 2023)
IntroductionThe present-day governance environment in the global arena has been impacted by social networks and the unique aspects of the era of the network society, leading to fundamental changes. These changes have transformed the governance environment "in", "on", and "through" social networks and made them an obvious and inevitable part of the picture. Therefore, this article aims to provide an effective and viable model for playing an authoritative role in the future of cyber operations at the international level. This will enable participants to take part in shaping the global cyber landscape. The objective of creating a desirable model for digital governance in the network society era has been outlined. By observing relevant documents and conducting library studies, methods used by other countries in this area have been obtained for the expansion and development of domestic and international governance. The two approaches of "open governance" and "control governance" have been examined and discussed, including the effects of adopting each approach and how they may impact international relations.The results of the current study demonstrate that though some might believe that open governance is the predominant approach in international arenas, a combination of both open and control governance based on the system of societal issues has a significant impact on cyber governance practices. Consequently, the ideal model of digital governance is a flexible authoritarian approach based on the system of issues that nations should adopt in both domestic and international arenas.The concepts of "digital governance" and "networked society" are two fundamental areas that constitute the new ecosystem and can be examined from multiple perspectives. The theory of network society, coined by Manuel Castells, presents a macro-level view of the characteristics of the current era, emerging as a new theory after the information society. The aforementioned theory can offer insights into the new age's characteristics.According to Castells, the transition to the network society is characterized by the polarization of international economic structures and societies, the transformation of work and employment, the evolution of media and audiences, the change of the material foundations of culture (the space of flows and timeless time), and the breakdown of the societal fabric. It is notable that the logic of the digital governance and network society areas are distinct, leading to contrasting identities. Ultimately, these identities exist on opposite ends of the spectrum, emphasizing the diverse nature of the network society.Furthermore, digital governance, as a significant aspect impacting global developments, has emerged as an all-encompassing framework for reforms within various governance domains. The digitization process will facilitate seamless cooperation between the public and private sectors, paving the way for effective digital governance, particularly through the reforming of public sector bills.Additionally, several experts assert that governments need to become more efficient and productive, engage in closer collaboration with stakeholders from diverse sectors, and leverage data to inform decision-making through the creation of evidence-based policies. Governments must also enhance transparency and accountability and respond to the evolving relationship between government and citizens by enhancing citizen participation through the implementation of public services or other measures. These concepts have led to the development of digital governance. However, the advancement of public sector improvements within Iran has been comparatively sluggish.The widespread usage of information and communication technologies in day-to-day life, as well as the increasing penetration of these technologies among households in the last few decades, have resulted in a significant amount of information generated about individuals, groups, and societies. In order to enhance their governance indicators, governments have no choice but to access, process, and make use of this information while managing and governing their communities. Consequently, the purpose of the current research is to review governance in the digital age and the research approach is descriptive-analytical. The findings showed that governments, in order to fulfill the changing needs and desires of their citizens, are compelled to make use of information technology to conduct reforms within the public sector and thus bring about radical changes in the way they deliver public services. Digital governance, with its tremendous power, plays an instrumental role in curtailing administrative paperwork, streamlining operations, restructuring governmental institutions, reducing the cost of governance, making governance more adaptable to changes, reducing bureaucratic corruption, enhancing public participation, increasing transparency within the government body, reducing decentralization, fortifying democratic foundations, reforming administrative and governmental bureaucracy, enhancing governance accountability, increasing efficiency and productivity, improving the quality of information and data accessibility, saving time, and enhancing the effectiveness of governance processes.The penetration and expansion of information and communication technology in all areas of human life has led to a change in the ways of communication between people and the society, the methods and procedures that the society contributes to each person in doing their work. Due to these changes, the current age is called the age of information and communication, as a result of which human communities have become scientific communities and citizens have become users of social networks. Today, the vital role of the government and government agencies in the development of the country and the well-being of citizens is obvious.The digital age has prompted many thinkers to propose various indicators of digital governance, which draw from theories and assumptions aiming to serve as the cornerstone of an efficient and user-centered system. Some experts have described e-government as the second revolution after modern government and public administration, affecting not only the methods of public service delivery but also the fundamental relationships between the government and the people. The transformation of the times also necessitates decentralizing operations, hiring subject-matter experts, outsourcing tasks to the private sector, and transforming local authorities into designers and supervisors. In addition, safeguarding the environment, strengthening the culture of citizenship, supporting various public spheres, and encouraging the private sector to reduce government ownership are some of the policies and requirements outlined in the sixth development plan. It is indispensable to carry out information acquisition, licensing, payments, and administrative and operational processes electronically, avoiding in-person procedures (Abdul Hosseinzadeh, 2019, p. 187).The Information Technology Governance Institute defines governance as "a set of responsibilities and activities carried out by the board of directors or senior managers in order to realize strategic direction, ensure the achievement of anticipated goals, manage the organization's risks, and allocate and control resources." Effective governance involves defining structures and mechanisms to ensure effective performance of responsibilities and duties, and it can lead to greater transparency and accountability in organizational functioning.In the field of digital governance, the definition of the concept is derived from the higher-level concept of governance. It can be defined as structures and mechanisms adopted by organizations in the field of digital transformation to optimize their resources and capabilities in terms of digital strategies, processes, and systems. The ultimate goal of effective digital governance is to maximize the positive impact of digital technologies on an organization's operations and service delivery, while minimizing the negative impacts (Bonet and Westerman, 2014).